If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2yi = 14 + -9i Reorder the terms: 2iy + 3x = 14 + -9i Solving 2iy + 3x = 14 + -9i Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '9i' to each side of the equation. 2iy + 9i + 3x = 14 + -9i + 9i Reorder the terms: 9i + 2iy + 3x = 14 + -9i + 9i Combine like terms: -9i + 9i = 0 9i + 2iy + 3x = 14 + 0 9i + 2iy + 3x = 14 Add '-3x' to each side of the equation. 9i + 2iy + 3x + -3x = 14 + -3x Combine like terms: 3x + -3x = 0 9i + 2iy + 0 = 14 + -3x 9i + 2iy = 14 + -3x Reorder the terms: -14 + 9i + 2iy + 3x = 14 + -3x + -14 + 3x Reorder the terms: -14 + 9i + 2iy + 3x = 14 + -14 + -3x + 3x Combine like terms: 14 + -14 = 0 -14 + 9i + 2iy + 3x = 0 + -3x + 3x -14 + 9i + 2iy + 3x = -3x + 3x Combine like terms: -3x + 3x = 0 -14 + 9i + 2iy + 3x = 0 The solution to this equation could not be determined.
| 17-6*x=47+10*x | | X-20x+2x+20=180 | | p-0.6*40=19 | | -17x=13x-28 | | 2-16t=6(-t+2) | | 6y+10=3y+y^2 | | 2x-1x+x+74=180 | | 16x+4=-4 | | (x-7)(x-2)(x-4)(x-5)=7x | | p-0.6*30=19 | | (5X^3+x^2+x-13)(x^2-1)= | | (2m-7n)(2m-3n)= | | -9(-2r-10s+3)= | | 2Inx-5Inx=6 | | 3x-1x+4x+13=180 | | 8(c-6)= | | (4x^2-6)(7x^2-7)= | | 5-3/2(6-2/3y) | | 13(x+5)= | | 3x+2=5x-18 | | y=3x^3-7x^2-14x+24 | | log5[5x/x-2]=2 | | 3b-5b=10 | | 3.25b-1.5=14.5 | | 3.25-1.5=14.5 | | 3(x-7)=63 | | Ln(x)=-90 | | 3(c-4)=3c-12 | | -6p+8+7p=12 | | 7r^2+10r-72=0 | | 2w=36+5w | | 7r^2+10-72=0 |